2019
DOI: 10.1093/ajcn/nqy371
|View full text |Cite|
|
Sign up to set email alerts
|

Infant milk-feeding practices and diagnosed celiac disease and inflammatory bowel disease in offspring: a systematic review

Abstract: Background During the Pregnancy and Birth to 24 Months Project, the USDA and US Department of Health and Human Services initiated an evidence review on diet and health in these populations. Objective The aim of these systematic reviews was to examine the relationships of never versus ever feeding human milk, shorter versus longer durations of any and exclusive human milk feeding, and feeding a lower versus a higher intensity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 39 publications
0
14
1
1
Order By: Relevance
“…3,14 In addition to gluten and genetics, other potential risk factors for CD such as types of infant milk consumption, mode of delivery, smoking, age at gluten intake, and early life exposure to infection have also been investigated. [19][20][21][22][23] In our study, the type of milk consumption during infancy did not show a significant association with GI and non-GI manifestations (table 6). Although some studies have suggested that breastfeeding has protective effects on CD, others do not support these protective effects.…”
Section: Clinical Features Of Celiac Diseasecontrasting
confidence: 51%
See 1 more Smart Citation
“…3,14 In addition to gluten and genetics, other potential risk factors for CD such as types of infant milk consumption, mode of delivery, smoking, age at gluten intake, and early life exposure to infection have also been investigated. [19][20][21][22][23] In our study, the type of milk consumption during infancy did not show a significant association with GI and non-GI manifestations (table 6). Although some studies have suggested that breastfeeding has protective effects on CD, others do not support these protective effects.…”
Section: Clinical Features Of Celiac Diseasecontrasting
confidence: 51%
“…Although some studies have suggested that breastfeeding has protective effects on CD, others do not support these protective effects. 19,20,22 A case-control study on milk powder consumption during the first two years of life in genetically susceptible children for CD showed that milk powder intake was not associated with CD in Swedish children. 24 Another case-control research found that CD was not Niknam et al statistically associated with the duration of breastfeeding, but was associated with skim milk consumption.…”
Section: Clinical Features Of Celiac Diseasementioning
confidence: 99%
“…The mode of delivery, breastfeeding, the environment, and the use of antibiotics in early life can affect GI microbiota development, and these factors occur mostly in perinatal and neonatal periods ( 9 ). Most of these factors have been recognized as potential triggers for IBD, nevertheless, related researches have focused mainly on the postnatal growth period ( 10 12 ). The early-life period includes the pregnancy period and the first 2 years of life, which can be classified into three stages: perinatal, lactation, and postweaning nutrition period.…”
Section: Introductionmentioning
confidence: 99%
“…Breastfeeding had no preventive effect on the development of CDA or CD during childhood according to the systematic review by Szajewska [ 67 ]. Only limited case-control evidence suggests that breastfeeding for short durations or not at all is associated with a higher risk of a diagnosis of IBD and celiac disease, respectively [ 76 ].…”
Section: Discussionmentioning
confidence: 99%